S = 2 2 − 1 2 2 + 1 + 3 2 − 1 3 2 + 1 + … + 2 0 1 6 2 − 1 2 0 1 6 2 + 1
If S denotes the value of the above expression, then find the value of ⌊ S ⌋ + 2 0 1 6 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Can't understand last line.
Log in to reply
I have added lines to the solution. See if it helps.
How did you figure out the fourth line of the solution. I know it's correct but what was the way to figure that out from the third line?
Log in to reply
Through practice. This is a common method used to make the summation telescopic. For example, n ( n + 1 ) 1 = n 1 − n + 1 1 and n ( n + 1 ) ( n + 2 ) 1 = ( n 1 − n + 1 2 + n + 2 1 ) . You may need to do trial and error to find out.
Log in to reply
Is it possible to do this with any expression in the denominator?
Log in to reply
@Anupam Nayak – Of course not all.
Log in to reply
@Chew-Seong Cheong – Then how do we determine if it is possible or not? Is there a way to check it because if it was not possible for that expression, we will waste a lot of time but with no results.
S = 2 2 − 1 2 2 + 1 + 3 2 − 1 3 2 + 1 + … + 2 0 1 6 2 − 1 2 0 1 6 2 + 1 = n = 1 ∑ 2 0 1 5 ( n + 1 ) 2 − 1 ( n + 1 ) 2 + 1 = n = 1 ∑ 2 0 1 5 n ( n + 2 ) ( n + 1 ) 2 + 1 = n = 1 ∑ 2 0 1 5 ( n 1 − n + 2 1 + 1 ) = n = 1 ∑ 2 0 1 5 n 1 − n = 3 ∑ 2 0 1 7 n 1 + n = 1 ∑ 2 0 1 5 1 = 1 + 2 1 + n = 3 ∑ 2 0 1 5 n 1 − n = 3 ∑ 2 0 1 7 n 1 + n = 1 ∑ 2 0 1 5 1 = 1 + 2 1 − 2 0 1 6 1 − 2 0 1 7 1 + 2 0 1 5 = 1 . 4 9 9 + 2 0 1 5 = 2 0 1 6 . 4 9 9 ⇒ ⌊ S ⌋ + 2 0 1 6 = 2 0 1 6 + 2 0 1 6 = 4 0 3 2
Problem Loading...
Note Loading...
Set Loading...
S ⇒ ⌊ S ⌋ + 2 0 1 6 = n = 2 ∑ 2 0 1 6 n 2 − 1 n 2 + 1 = n = 2 ∑ 2 0 1 6 n 2 − 1 n 2 − 1 + 2 = n = 2 ∑ 2 0 1 6 ( 1 + n 2 − 1 2 ) = n = 2 ∑ 2 0 1 6 ( 1 + n − 1 1 − n + 1 1 ) = n = 2 ∑ 2 0 1 6 1 + n = 2 ∑ 2 0 1 6 n − 1 1 − n = 2 ∑ 2 0 1 6 n + 1 1 = n = 1 ∑ 2 0 1 5 1 + n = 1 ∑ 2 0 1 5 n 1 − n = 3 ∑ 2 0 1 7 n 1 = 2 0 1 5 + 1 1 + 2 1 − 2 0 1 6 1 − 2 0 1 7 1 ≈ 2 0 1 6 . 5 = 2 0 1 6 + 2 0 1 6 = 4 0 3 2